REVITALISASI FUNGSI MASJID DALAM KEHIDUPAN MASYARAKAT MODERN - Rifa'i, Ahmad (IAIN Kediri, 2016)
Mosque is a worship place for Muslim, especially for conducting prayer. Mosque is often called as Baitullah (Allah house) which has main function as a prayer place, pray, reciting Al-Qur’an, recitation and others worships. By analyzing historical data, this article explains that in Rasulullah era and early Islam generation, mosque has larger function, not only as a worship place, but also as a center of community’s activities as like learning place, economy development center, politic development center, dakwah center, and moral development center. Therefore, in the early phase, mosque role is really strategies so that it needs to be a model of revitalization of mosque role in modern era. Keywords; Mosque, worship place, revitalization, activities center